Penjadwalan Produksi Pakan Ternak di PT Charoen Pokphand Indonesia Sepanjang - Tommy Alvianto Ongkodjojo; Herry Christian Palit (Jurnal Titra, 2014)
PT Charoen Pokphand Indonesia Sepanjang is an animal feed production company. Schedulling that is done by PPIC Departement focus only on animal feed code and quantity. Schedulling animal feed for every pellet machine do not arranged yet, so the setup time for every machine is high. Schedulling system updates had been done with LRPT (longest remaining processing time) method. Schedulling system that had been made can reduce the production setup time and time to finish all animal feed. The time to finish all animal feed can be reduced 4,87% after implemented schedulling system. Different time for company with schedulling system can produce 124,2 tonnage animal feed. Percentage setup machine decrease 5,88% for machine 1, 35,71% for machine 2 and 50% for machine 4. Percentage setup machine increase 22,22% for machine 3.